Effect of Organic Selenium-Enriched Yeast on Relieving the Deterioration of Layer Performance, Immune Function, and Physiological Indicators Induced by Heat Stress - Abbas, Ahmed O.; Alaqil, Abdulaziz A.; Mehaisen, Gamal M. K.; El Sabry, Mohamed I. (Frontiers in Veterinary Science, 2022)
Heat stress (HS) induces deleterious effects on the performance of laying hens and causes economic losses for poultry industry. The current study was carried out to investigate the effect of Selenium-enriched yeast (SY) on relieving the performance, immunity and physiological deterioration induced by heat stress in laying hens. A total of 324, 28-wk-old, Hy-Line brown commercial chicken layers were randomly distributed into 4 treatments according to a 2 × 2 factorial design, with 9 hens x 9 replicates per treatment (n= 81). From 30-34 wk of age, layers were exposed to 2 temperature treatments (HS treatment groups); a thermoneutral temperature at 24°C and a heat stress at 35°C. Layers were further assigned into 2 subgroups according to dietary supplementation with organic selenium-enriched yeast (SY treatment groups) at either 0 or 0.4 mg/kg diet. Results indicated that all aspects of the layer performance during the experimental period were impaired by exposure to HS, while SY supplementation improved the layer performance in both HS and non-HS layers. Intestinal villi disruptions and liver necrotic hepatocytes were observed in the layers exposed to HS while villi integrity and hepatocytic normality were enhanced by SY treatment. A significant (P<0.05) decrease in the total leukocytes count, anti-SRBC antibody titer, and T- and B-lymphocyte proliferation along with an increase in the heterophils/lymphocytes (H/L) ratio were observed in the HS layers compared to non-HS layers. On the contrary, SY treatment significantly (P<0.05) improved the immune function traits in both the HS-layers and non-HS layers. Furthermore, the SY treatment plays an important role in mitigating the oxidative stress and inflammation induced by HS, displaying lower levels of plasma corticosterone, lipid peroxidation, interleukin-1β and tumor necrosis factor-α in HS-layers supplemented with SY compared to HS-layers without SY supplementation. These results conclude that addition of SY to the diet of laying hens could be applied as a potential nutritional approach to relieve the deterioration effects of heat stress on the immunity, physiological status and productive performance of laying hens.